Identification of Small-Molecule Frequent Hitters of Glutathione S-Transferase–Glutathione Interaction. (July 2016) - Brenke, Jara K.; Salmina, Elena S.; Ringelstetter, Larissa; Dornauer, Scarlett; Kuzikov, Maria; Rothenaigner, Ina; Schorpp, Kenji; Giehler, Fabian; Gopalakrishnan, Jay; Kieser, Arnd; Gul, Sheraz; Tetko, Igor V.; et al.
In high-throughput screening (HTS) campaigns, the binding of glutathione S-transferase (GST) to glutathione (GSH) is used for detection of GST-tagged proteins in protein-protein interactions or enzyme assays. However, many false-positives, so-called frequent hitters (FH), arise that either prevent GST/GSH interaction or interfere with assay signal generation or detection. To identify GST-FH compounds, we analyzed the data of five independent AlphaScreen-based screening campaigns to classify compounds that inhibit the GST/GSH interaction. We identified 53 compounds affecting GST/GSH binding but not influencing His-tag/Ni 2+ -NTA interaction and general AlphaScreen signals. The structures of these 53 experimentally identified GST-FHs were analyzed in chemoinformatic studies to categorize substructural features that promote interference with GST/GSH binding. Here, we confirmed several existing chemoinformatic filters and more importantly extended them as well as added novel filters that specify compounds with anti–GST/GSH activity. Selected compounds were also tested using different antibody-based GST detection technologies and exhibited no interference clearly demonstrating specificity toward their GST/GSH interaction. Thus, these newly described GST-FH will further contribute to the identification of FH compounds containing promiscuous substructures. The developed filters were uploaded to the OCHEM website (http://ochem.eu ) and are publicly accessible for analysis of future HTS results.